2018
DOI: 10.1007/s00431-018-3224-9
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of body mass index in children with type 1 diabetes mellitus

Abstract: The prevalence of childhood overweight and obesity has risen during the last 30 years, not only in children with type 2 diabetes, but also those with type 1 (T1D) and this is linked with an increased cardiovascular risk. A better understanding of weight patterns in the years after diagnosis of T1D is important to identify those children with a risk for excess weight gain and strategies to decrease this. We retrospectively analyzed data of all children with T1D followed at the department of Pediatric Endocrinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 16 publications
5
32
0
1
Order By: Relevance
“…In our study, we found that that girls with T1D had higher BMI Z‐score compared with both boys with T1D and healthy peers. This observation was in concordance with several other studies including a very large study, investigating BMI Z‐score in 11.500 children and adolescents with T1D from Denmark, Iceland, Norway, and Sweden . In our study, BMI Z‐score correlated negatively to CTX Z‐score (and not OCN Z‐score) which could explain why CTX Z‐score was significantly lower in girls compared with boys, as girls had significantly higher BMI Z‐scores compared with the boys with T1D.…”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found that that girls with T1D had higher BMI Z‐score compared with both boys with T1D and healthy peers. This observation was in concordance with several other studies including a very large study, investigating BMI Z‐score in 11.500 children and adolescents with T1D from Denmark, Iceland, Norway, and Sweden . In our study, BMI Z‐score correlated negatively to CTX Z‐score (and not OCN Z‐score) which could explain why CTX Z‐score was significantly lower in girls compared with boys, as girls had significantly higher BMI Z‐scores compared with the boys with T1D.…”
Section: Discussionsupporting
confidence: 93%
“…The latter can interact with T1D duration, making DD a time‐dependent condition. Even those with initial good insulin sensitivity and no genetic predisposition may transition to DD secondary to unhealthy lifestyle that leads to weight gain . While genetic predisposition is non‐modifiable, environmental factors can be controlled, thus limiting the prevalence of DD.…”
Section: Pathogenesis Of Ddmentioning
confidence: 99%
“…Even those with initial good insulin sensitivity and no genetic predisposition may transition to DD secondary to unhealthy lifestyle that leads to weight gain. 47 While genetic predisposition is non-modifiable, environmental factors can be controlled, thus limiting the prevalence of DD. Exposure to obesogenic environments affects the rate of overweight and obesity, particularly among children.…”
Section: Prevalence Of Dd According To Each Definitionmentioning
confidence: 99%
“…However, there is increasing interest in OSA in patients with T1D, particularly that some recent studies suggest that OSA in T1D might be more related to autonomic neuropathy rather than obesity (158). In addition, epidemiological studies suggest that obesity prevalence is increasing in patients with T1D which might further increase their risk of developing OSA (159).…”
Section: Osa and T1dmentioning
confidence: 99%
“…IH, intermittent hypoxia; RAAS, renin-angiotensin-aldosterone system; RH, resistant hypertension; PA, primary aldosteronism; MR, mineralocorticoid receptors. In rodent studies, IH promoted angiotensin I and AT1 expression, increased the activation of the carotid body by angiotensin II and resulted in increased renin and aldosterone levels leading to increased BP (159,169,170). In addition, oxidative stress has been shown to increase the activation of the mineralocorticoid receptors (MR) in rodent models (171).…”
Section: Osa and The Renin-angiotensin-aldosterone System (Raas)mentioning
confidence: 99%